Implications of Shrimp Crackers Empowerment Industry on Community Welfare - Afriyanti, Riska; Daraba, Dahyar; Kasmita, Maya (Universitas Negeri Makassar, 2018)
The aim of development is to realize an Indonesian society that is peaceful, just, democratic, competitive, advanced and prosperous in the Unitary Republic of Indonesia. The purpose of this study is to determine the extent to which the government runs the shrimp cracker industry empowerment program, the area of the marketing of shrimp cracker industry products, and the impact of the shrimp cracker industry on the welfare of the industrial owner. The method used in this study is a qualitative method that is descriptive-inductive approach by providing a systematic, factual and accurate description in the presentation of reports, based on the results of research conducted. Based on the results of research and data management, it can be concluded that community empowerment carried out by DISKOPERINDAG has not been maximized. There is no capital assistance or means of production from the government so that it becomes a major problem for the community to start a business. In the implementation of empowerment also occurs obstacles from the community itself such as the mindset of people who have not developed due to low education. The area of marketing of production is limited because there is no business from the owner of the industry itself. The existence of shrimp cracker industry has a positive impact on society by increasing the community's economy. The community can meet personal and family needs from the results of this shrimp cracker industry. From this it can be said that people's welfare has increased after the shrimp cracker industry.